Acurácia de testes neurocognitivos para o diagnóstico de doença de Alzheimer em pacientes com biomarcadores no líquido cefalorraquidiano - Patrícia Regina Henrique Peles (2021)
ABSTRACT Introduction: Alzheimer's disease (AD) is the main neurodegenerative disease, particularly common among older adults and the leading cause of dementia worldwide, although underreported in many countries. The diagnosis of AD in clinical practice until recently was based exclusively on the identification of a characteristic cognitive profile and the exclusion of other diseases by complementary exams. In recent years, important advances in diagnosis have been achieved with the development of specific biomarkers for the disease. Among these biomarkers are the dosages of beta-amyloid proteins (Aβ), total tau (T-tau) and phosphorylated tau (P-tau) in the cerebrospinal fluid (CSF), Aβ has its concentration reduced in the CSF, while T-tau and P-tau have increased concentrations in patients with the disease. The study of biomarkers in the CSF or, by molecular neuroimaging methods, allows the biological diagnosis of AD and its differentiation from non-AD dementias through the AT(N) classification system. According to this classification, A + individuals, regardless of whether T and (N) are + or -, are qualified as presenting the continuum of the pathological process of AD. Unfortunately, however, the diagnostic biomarkers of AD are costly or obtained by an invasive method (such as lumbar puncture), in addition are not unavailable in many centers. Thus, the diagnostic methods most used in clinical practice for diagnosing AD are cognitive assessment, laboratory tests and neuroimaging. The cognitive screening tests and the neuropsychological assessment battery are widely used in the clinical environment to identify dementias, in particular AD. Several studies have already investigated its psychometric characteristics and accuracy, mainly in Brazil. However, most have not been investigated or validated in patients with a biological diagnosis of AD, which could increase the current evidence for its use in clinical practice. Study 1: Objectives: To investigate the accuracy of the Brief Cognitive Screening Battery (BCSB) in the differential diagnosis between AD, non-AD cognitive impairment (both defined by cerebrospinal fluid-CSF biomarkers) and healthy cognition, and to correlate CSF biomarker results with cognitive performance. Methods: Overall, 117 individuals were evaluated. Forty-five patients with cognitive impairment or mild dementia within the prodromal AD continuum defined by the AT(N) classification [A+T+/- (N)+/], 27 non-AD patients with MCI or mild dementia [A-T+/-(N)+/-], and 45 cognitively healthy individuals without CSF biomarkers results. All participants were submitted to the BCSB. Results: Total BCSB score and delayed recall (DR) of the BCSB memory test showed high diagnostic accuracy, as indicated by areas under the ROC curve (AUC), namely 0.89 and 0.87, respectively, for discrimination between AD and non-AD versus cognitively healthy controls. Similarly, total BCSB and DR displayed high accuracy (AUC-ROC curves of 0.89 and 0.91, respectively) for differentiation between AD and controls. BCSB tests displayed low accuracy for differentiation between AD and non-AD. CSF levels of biomarkers correlated significantly, though weakly, with DR. Conclusions: Total BCSB and DR scores presented good accuracy in the differentiation between patients with AD biological diagnosis and cognitively healthy individuals, but low accuracy to differentiate AD from non-AD patients. Study 2: Objectives: To investigate the accuracy of common neuropsychological tests used in the clinical setting for the diagnosis of AD defined by cerebrospinal fluid (CSF) biomarkers and AT(N) classification. Methods: Seventy four patients participated in the study, namely 42 with diagnosis of AD continuum [A+T+/-(N)+/-] and 32 non-AD patients [A-T+/-(N)+/-]. The two groups were matched for age, sex and schooling. All participants were submitted to a thorough neuropsychological assessment with the following instruments: Mattis Dementia Rating Scale (DRS), Rey's Auditory Verbal Learning Test (RAVLT), the Boston naming-Consortium to Establish a Registry for Alzheimer’s Disease, a reduced version of the CERAD, Digit Span Forward (DSF), Digit Span Backward (DSB) and Cubes from The Wechsler Adult Intelligence Scale (WAIS), verbal fluency – animals (VF-A), and FAS. Results: The Memory (MEM) and Initiative/Perseveration (I/P) subscales of the DRS, FAS, Digit Span Backward (DSB) and Boston naming displayed good discrimination between AD and non-AD patients. The MEM subscale of the DRS, RAVLT A6 and FAS presented high sensitivity (90% or more) for AD diagnosis, while DSF displayed high specificity. Non-AD patients had greater difficulty in FAS, DSB and in Boston naming. Conclusions: Performance of patients with biological diagnosis of AD on MEM and I/P of DRS, and RAVLT A7 was significantly different from that of non-AD subjects. However, no neuropsychological test displayed high accuracy for differentiation between AD and non-AD patients.